Home care nurse health strategy family - Maria Fernanda Pereira Gomes; Lislaine Aparecida Fracolli; Bruno César Machado (O Mundo da Saúde, 2015)
The Family Health Strategy (FHS) aims at the reorganizing of primary health care in the country and requires a home visit as an interaction technology in health care. It is an important tool for nurses, since it is the intervention that enables us to approach to the determinants of the health illness in the family. In this context the role of a nurse should be ethical and legal, empowering families who are in vulnerable condition to fight for their health rights. However, the objective of this research is to evaluate the satisfaction of users of the Health Strategy Family in the municipality of Assis – SP in the perspec- tive of home care performed by nurses. This is a quantitative study in which they were used statistical analysis criteria for results evaluation and description. Data collection was carried out through home visits, and it is available a questionnaire with closed questions designed to evaluate the home care performed by nursing professionals. One-hundred participants took place in the survey. They were users who utilize the FHT services. In this study the majority of respondents said that the nurse is only seen when prompted. However, the nurse faces bureaucratic activities of overwork which prevents him from making and program home care, which is as great loss to the people and society as a whole, not have the evaluation of a professional peculiar look peculiar like a nurse.